Stress-based structural topology optimization for design-dependent self-weight loads problems using the BESO method. Issue 2 (1st February 2023) - Garcez, Gisele L.; Pavanello, Renato; Picelli, Renato
Abstract : This article aims to propose an approach to the stress-based topology optimization of continuous elastic bi-dimensional structures subjected to design-dependent self-weight loads using the Bi-directional Evolutionary Structural Optimization (BESO) method. Topology optimization is developed through the minimization of P -norm von Mises stress while satisfying a volume constraint. To implement the algorithm, a consistent sensitivity analysis including design-dependent loads has been developed by the adjoint method. A series of tests has been performed to explore and validate the method through three numerical examples: an L-bracket; a doubly supported beam with one pre-existing crack notch; and a cantilever beam. Comparison between traditional compliance minimization and stress minimization analyses, including design-dependent self-weight loads, shows that the method is an effective way to reduce the maximum stress.